2008
DOI: 10.1111/j.1365-2125.2008.03183.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of aspirin resistance: a comprehensive systematic review

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • A genetic basis for aspirin resistance has been postulated to exist. • The individual studies published have been too small to allow reliable conclusions to be drawn. • In order to clarify what, if any, genetic basis exists for aspirin resistance, we have undertaken, to our knowledge, the largest and most comprehensive systematic review conducted to‐date in this field. WHAT THIS STUDY ADDS • There is a significant association between the PlA1/A2 molecular variant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
0
10

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(133 citation statements)
references
References 58 publications
3
120
0
10
Order By: Relevance
“…Although the response to aspirin appears to be heritable in certain families with strong family history of coronary heart disease, 27 studies investigating genetic polymorphism as an explanation for aspirin resistance have so far been conflicting. 28 Interestingly, among high-risk black and white families with strong family history of heart disease, aspirin response via COX-1-independent pathways appears to be more heritable than response by COX-1-dependent pathways. 27 Platelet turnover is another mechanism postulated to contribute to aspirin resistance.…”
Section: Mechanisms Of Aspirin Resistancementioning
confidence: 99%
“…Although the response to aspirin appears to be heritable in certain families with strong family history of coronary heart disease, 27 studies investigating genetic polymorphism as an explanation for aspirin resistance have so far been conflicting. 28 Interestingly, among high-risk black and white families with strong family history of heart disease, aspirin response via COX-1-independent pathways appears to be more heritable than response by COX-1-dependent pathways. 27 Platelet turnover is another mechanism postulated to contribute to aspirin resistance.…”
Section: Mechanisms Of Aspirin Resistancementioning
confidence: 99%
“…In addition, numerous studies have investigated the role of genetic factors that contribute to the resistance or augmented response to aspirin 14,15) ; however, they have conflicting results. A systematic review revealed that the PlA1/A2 variant is significantly associated with AR, but no significant association was found with AR in polymorphisms of COX-1, GPla, P2Y1, or P2Y12 genes 16) . Aspirin leads to COX-1 inactivation and decreased TXA2 production, achieving the goal of antithrombotic therapy 17) .…”
Section: Study Populationsmentioning
confidence: 99%
“…COX -1 enzyme gene, P2Y1 and P2Y12 platelet receptor genes and glycoprotein (GP) IIb/IIIa genes are most studied genes in aspirin resistance, but there are conflicting results regarding association of aspirin non-response and gene polymorphism (19)(20)(21). A meta-analysis of 31 studies examining 50 polymorphisms in 11 genes showed that only GPIIIa gene polymorphism was associated with aspirin resistance (22).…”
Section: Possible Causes Of Aspirin Resistancementioning
confidence: 99%